The influence of orifice insertionin radial swirling flow for low emissions combustion - Ishak, Mohmad Shaiful Ashrul; Mohd. Jaafar, Mohammad Nazri (Faculty of Mechanical Engineering, 2008)

(untitled)
This paper presents the effect of inserting swirler outlet orifice plate of different sizes at the exit plane of the flat blade radial air swirler in liquid fuel burner system. Tests were carried out with three different orifice plates with area ratios (orifice area to swirler exit area ratio) between 1.0 to 0.7 using 280 mm inside diameter combustor of 1000 mm length. Tests were conducted using commercial diesel as fuel. Fuel was injected at the back plate of the 60o vane angle swirler outlet using central fuel injector with single fuel nozzle pointing axially outwards. The aim of the insertion of orifice plates was to create the swirler pressure loss at the swirler outlet phase so that the swirler outlet shear layer turbulence was maximised to assist with fuel/air mixing. In the present work, orifice plate with smaller area ratios exhibited very low NOX emissions for the whole operating equivalence ratios. NOX reduction of more than 15 percent was achieved for orifice with 0.7 area ratio compared to area ratio of 1.0. Other emissions such as carbon monoxide increased with decreasing in orifice area ratios. This implies that good combustion was achieved using smallest area ratios of orifice plate.